EFL STUDENTS’ KAHOOT! EXPERIENCE: PERSPECTIVES FROM INDONESIAN SECONDARY SCHOOL STUDENTS IN LANGUAGE LEARNING - Meita Dwi Putri Angelita; Nabilla Purnama Asri; Afida Annisa; Wendi Kusriandi; Nunung Nurjannah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
The use of technology into English language learning is becoming more and more vital for keeping students interested and motivated. Kahoot! is a gamified learning platform that provides dynamic and enjoyable learning experiences across a range of technical instruments. Nonetheless, studies examining students' firsthand experiences with Kahoot! in EFL (English as a Foreign Language) classrooms in Indonesia are still scarce. This study seeks to investigate the experiences of intermediate-level EFL students utilising Kahoot! as a tool for English language acquisition and to ascertain how its characteristics enhance motivation, engagement, and comprehension of the educational content. A descriptive qualitative methodology was utilised, gathering data via questionnaires and semi-structured interviews with 21 Grade 11 students from a senior high school governed by the Ministry of Religious Affairs in Cirebon Regency. The results show that Kahoot! makes the classroom more fun and interactive, helps students stay focused, and helps them understand better. Also, gamification features like competition, awards, and rapid feedback really encourage kids to become involved. These findings indicate that Kahoot! can function as an efficacious technology-driven pedagogical approach that fosters student-centered education and encourages constructive learning dispositions within the Indonesian EFL setting.